Synthesis and spectral studies of nitrogen-oxygen donor macrocyclic metal complexes of Mn(II), Cu(II) Zn(II), Pd(II) and Pt(II) - Chandra, Sulekh; Verma, Shweta; Meera, P. (Journal of the Indian Chemical Society, 2008)
The complexes of Mn(II), Cu(II), Zn(II), Pd(II) and Pt(II) with a nitrogen-oxygen donor macrocyclic ligand, viz. 5,6,13,14-dibenzo[1,4,8,11]dioxadiaza-5,7,11,13-cyclotetradecin have been synthesized and characterized by elemental analysis, molar conductance, magnetic susceptibility measurements, spectral and electrochemical studies. The molar conductance measurements of the complexes in DMF solution correspond to non electrolytic nature for M(L)X(2) complexes and 1 : 2 electrolytes for M `(L)X(2) Complexes [where M = Mn(II), Cu(II); M ` = Zn(II), Pd(II) and Pt(II); X = Cl(-), NO(3)(-), and L = ligand]. Thus, the complexes may be formulated as [M(L)X(2)] and [M `(L)]X(2) respectively. Mn(II), Cu(II) complexes were of the high-spin type whereas the complexes of Zn(II), Pd(II) and Pt(II) were diamagnetic. On the basis of spectral studies an octahedral geometry has been assigned for Mull, tetragonal for Cull, tetrahedral for Zn(II) complexes whereas square planar for Pd(II) and Pt(II) complexes.
Keywords: Cu(II); macrocyclic; Mu(II); Pd(II); Pt(II); Zn(II)

Insights from a pan India Sero-epidemiological survey (Phenome-India Cohort) for SARS-CoV2 - Naushin, Salwa; Sardana, Viren; Ujjainiya, Rajat; Bhatheja, Nitin; Kutum, Rintu; Bhaskar, Akash Kumar; Pradhan, Shalini; Prakash, Satyartha; Khan, Raju; Rawat, Birendra Singh; Tallapaka, Karthik Bharadwaj; Anumalla, Mahesh; et al. (eLife, 2021)
To understand the spread of SARS-CoV2, in August and September 2020, the Council of Scientific and Industrial Research (India) conducted a serosurvey across its constituent laboratories and centers across India. Of 10,427 volunteers, 1058 (10.14%) tested positive for SARS-CoV2 anti-nucleocapsid (anti-NC) antibodies, 95% of which had surrogate neutralization activity. Three-fourth of these recalled no symptoms. Repeat serology tests at 3 (n = 607) and 6 (n = 175) months showed stable anti-NC antibodies but declining neutralization activity. Local seropositivity was higher in densely populated cities and was inversely correlated with a 30-day change in regional test positivity rates (TPRs). Regional seropositivity above 10% was associated with declining TPR. Personal factors associated with higher odds of seropositivity were high-exposure work (odds ratio, 95% confidence interval, p value: 2.23, 1.92-2.59, <0.0001), use of public transport (1.79, 1.43-2.24, <0.0001), not smoking (1.52, 1.16-1.99, 0.0257), non-vegetarian diet (1.67, 1.41-1.99, <0.0001), and B blood group (1.36, 1.15-1.61, 0.001).